2015
DOI: 10.1021/acsami.5b03431
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Multipass Caliber-Rolled Ti Alloy with Dexamethasone-Loaded Graphene for Dental Applications

Abstract: Titanium (Ti) and its alloys with a high mechanical strength and a small diameter can be effectively exploited for minimally invasive dental implantation. Here, we report a multipass caliber-rolled Ti alloy of Ti13Nb13Zr (MPCR-TNZ) with a high mechanical strength and strong fatigue characteristics. For further dental applications, MPCR-TNZ was surface-modified with reduced graphene oxide (RGO) and loaded with osteogenic dexamethasone (Dex) via π-π stacking on the graphitic domain of RGO. The Dex-loaded RGO-MPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 28 publications
1
73
0
Order By: Relevance
“…Such a large dimension enables the caliber-rolled rod to be directly used in the industry. Indeed, the authors fabricated a dental implant fixture with this material, which exhibited satisfying mechanical strength and fatigue resistance both in ambient atmosphere and simulated body fluid [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a large dimension enables the caliber-rolled rod to be directly used in the industry. Indeed, the authors fabricated a dental implant fixture with this material, which exhibited satisfying mechanical strength and fatigue resistance both in ambient atmosphere and simulated body fluid [21].…”
Section: Methodsmentioning
confidence: 99%
“…Since Kimura et al [11] reported the considerable mechanical improvement in a caliber-rolled low-alloy steel, related studies have been actively carried out with various materials [12][13][14][15][16][17][18][19]. Nevertheless, studies on caliber-rolled titanium alloys have just begun in spite of its importance both in academia and industry [20][21][22]. A UFG bulk rod was successfully manufactured by caliber-rolling Ti-6Al-4V alloy in this work.…”
Section: Introductionmentioning
confidence: 98%
“…53 The type of the MSCs in fifteen studies 19,32,36,40,[54][55][56][57][58][59][60][61][62][63][64] was not defined. Sixteen studies used preosteoblast cells, 14,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] including mouse osteoblastic cells 14, 65-74, 77-82 (MC3T3-E1) and rat calvarial osteoprogenitors, 75 while the type of the preosteoblast cells in one study 76 was not defined. Five articles 13, 83-86 used osteoblasts.…”
Section: Cell Sourcesmentioning
confidence: 99%
“…Graphene has unique physiochemical features, especially its potential for osteogenic induction of stem cells, that make it a promising material for promoting surface modification and bioactive character of metal-based composites. 48 Several studies 13,26,28,45,47,50,65,69,71,76,86,89,92 raised a debate regarding the influential role of metals combined with graphene on cell proliferation and viability.…”
Section: Graphene and Metalsmentioning
confidence: 99%
“…14,15 It is noted that the WR Ti-13Nb-13Zr exhibited the superior tensile properties in comparison to other forms of Ti-13Nb-13Zr alloy as discussed in our previous work; the WR alloy exhibited a tensile stress of 1,050 MPa, while both HR alloy and ASTM Ti-13Nb-13Zr possessed the value of 850 MPa. 16,17 Moreover, the WR alloy exhibited the higher hardness (HV 335±5) than the HR alloy (HV 215±4) as well as the solution-treated and cold-rolled sample (HV 285±7). 18 This is understood by the conclusion that Ti-13Nb-13Zr exhibits a higher hardness when it consists of the finer microstructural features.…”
mentioning
confidence: 98%